A NEW LASER APPROACH FOR SEISMIC RISK ASSESSMENT - BRITSKY, Oleksander; SHCHERBYNA, Serhii; PIGULEVSKIY, Petro; LISOVIY, Yurii; CHEREVKO, Iryna (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
In Europe, many countries have territories with the seismotectonic active areas – Italy, Greece, Romania etc. As we know, the special government and commercial organizations made many attempts to solve the seismic risk assessment problems in these countries using many different devices for solving these problems by estimating the seismic risk. All popular in all European countries specific devices are divided into two basic groups for solving the seismic risk assessment – accelerometers and velocimeters. For solving scientifically important tasks of the seismic risk assessment, there are no other high sensitivity devices for measurement of the displacements in countries with high level of the seismicity. These problems are based on difficulty for business to produce effective devices for measuring the displacement. These problems are based on influences of the temperature on mechanical and electronics instabilities of systems for measurement of the displacement. The cost of devices for measurement of the displacement with temperature stabilization may be higher than for devices of measurement of velocity or acceleration. Broadband seismometers with very high exactness of measurements of seismic events of any type can be afforded by the countries with high financial achievements only. However, there are other more important problems for measurements of the displacement beside acceleration or velocity for any places where there are seismic active zones.
Keywords: laser devices; seismicity; risk assessment; hazard areas; building; statistical estimation